Lonely Roads - Moore, William Ifeanyi (Bookvine (Vine Media Services), 2015)
Afam Udemba is an outcast in early 19th Centruty Aboh seeking escape from loneliness. He finds himself in a relationship with Adaobi, the daughter of Onwa- a powereful slave merchant but unfortunately, her father plans to strengthen his family ties with the royals by marrying her off to the Obi's son. As their love affair grows, Afam finds himself in the danger of being killed or being sold into slavery. In a world where social class and reputation is everything, all must decide how far they are willing to go and get what they want.
Keywords: Fiction